2009
DOI: 10.1177/1753193408098904
|View full text |Cite
|
Sign up to set email alerts
|

The Gigogne Flap: An Original Technique for an Optimal Pulp Reconstruction

Abstract: The reconstruction of digital pulp defects is still a challenge in hand surgery. Several reconstructive techniques are available, but in some cases, their advancement capacities are not sufficient for the flap to cover the whole defect. The Gigogne flap is a new, very simple and safe technique. It consists of harvesting two cutaneous flaps successively on the same neurovascular digital palmar bundle. The first plasty may be chosen among the well-known flaps usually applied in pulp reconstruction. The second pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…The abstract and title review narrowed the field to 124 studies that underwent full text review. Upon further review, 38 studies met the inclusion/exclusion criteria [19, 1218, 21, 22, 2530, 32, 35, 37, 3941, 4347, 49, 50, 52] (Table 1). The included studies were published between 1972 and 2011, and a total of 1,009 fingertip amputations were treated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The abstract and title review narrowed the field to 124 studies that underwent full text review. Upon further review, 38 studies met the inclusion/exclusion criteria [19, 1218, 21, 22, 2530, 32, 35, 37, 3941, 4347, 49, 50, 52] (Table 1). The included studies were published between 1972 and 2011, and a total of 1,009 fingertip amputations were treated.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published between 1972 and 2011, and a total of 1,009 fingertip amputations were treated. Twenty-seven studies reported 2PD outcomes [2, 3, 6, 8, 9, 14, 16, 18, 21, 2527, 29, 30, 32, 35, 37, 3941, 43, 4547, 49, 50, 52], 20 studies reported cold intolerance outcomes [13, 6, 7, 9, 14, 17, 22, 28–30, 39, 41, 43–45, 47, 49, 50, 52], eight studies reported AOM outcomes [5, 9, 21, 22, 40, 43, 44, 50], and 18 studies reported return-to-work time [4, 7, 1217, 21, 22, 25, 28, 29,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small soft tissue defects that require less than 5 mm of advancement can be covered readily by local advancement with palmar V-Y plasty, bilateral V-Y plasty, or modifications thereof [14][15][16] . The choice is based on the preference and experience of the surgeon, as all flaps are equally effective.…”
Section: Smaller Than 50% Of the Pulp Surfacementioning
confidence: 99%
“…137 The Gi-gone flap harnesses an island pedicle-based axial supply in a double V-Y advancement reminiscent of Atasoy's concept. 138 Boomerang flaps combine the concepts of reversed flow and perforator flaps. 139 Even smaller and more technically challenging island flaps have arisen with the digital artery perforator flaps.…”
Section: To the 2010smentioning
confidence: 99%